2018
DOI: 10.3892/etm.2018.6699
|View full text |Cite
|
Sign up to set email alerts
|

Eupatilin inhibits microglia activation and attenuates brain injury in intracerebral hemorrhage

Abstract: Inflammation serves a critical role in the pathophysiology of intracerebral hemorrhage (ICH)-induced brain injury. Eupatilin, a pharmacologically active flavone derived from Artemisia sp., has been reported to have antioxidant, anti-inflammatory, anti-allergic and antitumor activities. However, the effect of eupatilin in ICH has not been well studied. The aim of the present study was to investigate the effect of eupatilin on ICH-induced microglial inflammation. The MTT and Transwell migration assay results rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…CaiWait [41]Using Shengdi Dahuang Decoction to interfere with collagenase induced cerebral hemorrhage in a rat model, it was found that Shengdi Dahuang Decoction could reduce the expression of microglia around the cerebral hemorrhage, thereby reducing inflammatory factors.NF-κB,TNF-alphaand IL-1betarelease and improve the inflammatory response.QiaoWait [42]The study found that Artemisia annua extract iszelanflavin can inhibit the migration of microglia and reduce the lysis-induced red blood cell lysis.BV2inflammatory cytokines in cells NF-κB production and intracellular reactive oxygen species levels. Lan Wait [16] Fibrocystin was found to reduce classically activated M1number of microglia, but did not affect theM2the number of microglia; M1relatedTNF-alpha, IL-1beta, IL-6, iNOSdown-regulation of inflammatory substances, andTLR4pathway inhibition.…”
Section: Anti-injury-promoting Effects Of Traditional Chinese Medicin...mentioning
confidence: 99%
“…CaiWait [41]Using Shengdi Dahuang Decoction to interfere with collagenase induced cerebral hemorrhage in a rat model, it was found that Shengdi Dahuang Decoction could reduce the expression of microglia around the cerebral hemorrhage, thereby reducing inflammatory factors.NF-κB,TNF-alphaand IL-1betarelease and improve the inflammatory response.QiaoWait [42]The study found that Artemisia annua extract iszelanflavin can inhibit the migration of microglia and reduce the lysis-induced red blood cell lysis.BV2inflammatory cytokines in cells NF-κB production and intracellular reactive oxygen species levels. Lan Wait [16] Fibrocystin was found to reduce classically activated M1number of microglia, but did not affect theM2the number of microglia; M1relatedTNF-alpha, IL-1beta, IL-6, iNOSdown-regulation of inflammatory substances, andTLR4pathway inhibition.…”
Section: Anti-injury-promoting Effects Of Traditional Chinese Medicin...mentioning
confidence: 99%
“…Of course, increasing the M2/M1 phenotypic proportion of microglia usually brings more satisfactory results (Wang J. et al, 2018 ; Bai et al, 2020 ), and it has become the most frequently studied therapeutic method. Relying on the aforementioned targets, experimental therapeutic studies on the precise regulation on microglia phenotype are developing rapidly, and relevant drugs are summarized in Table 3 (Hu et al, 2011 ; Ohnishi et al, 2013 , 2019 ; Yang et al, 2014a , b , 2018 ; Iniaghe et al, 2015 ; Zhao et al, 2015a , b , 2018 ; Flores et al, 2016 ; Shi et al, 2016 ; Sukumari-Ramesh and Alleyne, 2016 ; Zhang et al, 2016 ; Anan et al, 2017 ; Chen-Roetling and Regan, 2017 ; Lan et al, 2017a ; Wang J. et al, 2017 ; Wei et al, 2017 ; Xu et al, 2017 ; Zeng et al, 2017 ; Chen C. et al, 2018 ; Chen S. et al, 2018 ; Fu et al, 2018 ; Han et al, 2018 ; Li X. et al, 2018 ; Qiao et al, 2018 ; Ren et al, 2018 ; Wang et al, 2018b ; Liang et al, 2019 ; Song and Zhang, 2019 ; Xi et al, 2019 ; Zhou F. et al, 2019 ; Cheng et al, 2020 ; Ding et al, 2020 ).…”
Section: Polarization Mechanism Of Microglia After Ichmentioning
confidence: 99%
“…Microglia are widely recognized as the earliest inflammatory cells that respond to ICH ( Wang, 2010 ; Yang et al, 2015a ). Cumulative research clarifies that microglia differentiation exerts pivotal functions in the pathogenesis and progression of ICH ( Qiao et al, 2018 ; Giordano et al, 2020 ). Upon activation, microglia polarize into different phenotypes that contribute differently to neuroinflammation in brain disease models ( Walker and Lue, 2015 ).…”
Section: Introductionmentioning
confidence: 99%